PENGARUH MOTIVASI BELAJAR DAN MINAT BELAJAR TERHADAP MAHASISWA UNIVERSITAS BHAYANGKARA JAKARTA RAYA - Zidan Fadliansyah, Fadel Muhammad Fadillah, Bambang Sampoerno, Maikel Felix Siahaan, Dian Sudiantini (CV. ADIBA AISHA AMIRA, 2024)
This study aims to determine the effect of learning motivation and interest in learning on students of Bhayangkara University, Greater Jakarta. This study uses a quantitative approach with a focus on the population of students at the university. The data analysis method used is descriptive statistical analysis to determine the impact of these variables on student academic achievement. The findings of this study are expected to explain the relationship between learning motivation, learning interest, and academic achievement of Bhayangkara University students in Greater Jakarta.